Mexico : Staff Report for the 2003 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This 2003 Article IV Consultation highlights that Mexico's real GDP remained subdued in the first half of 2003, with growth of 1.4 percent in the four quarters ending in the second quarter. While recent indicators of activity have been mixed, most observers still expect the economy to recover in the second half of the year, in line with the United States recovery. The government has made significant progress in strengthening the structure of public debt. Public external debt has fallen further from 15 percent of total debt in 2000 to 13 1\2 percent in 2002.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet